Menghasilkan Materi Pembinaan Iman Anak Sekolah Minggu Melalui Pengenalan Karakter Allah - Karuniawati, Naumi (Shift Key : Jurnal Teologi dan Pelayanan, 2024)
Recently there has been an increase in cases of bullying perpetrated by children, therefore the development of faith in children needs to be paid attention to in order to develop children's character and spirituality. Building faith in children by introducing the character of God, helping children know God's character, correctly interpreting that they were created in the image and likeness of God, and orienting themselves towards being like God. Therefore, research was carried out to prepare faith formation material for children which aims to introduce the character of God. The research method used is Research and Development (R&D) Level 1 with the aim of designing a faith formation module about the character of God based on the books of Genesis, Exodus, Leviticus, Bialangan and Deuteronomy. The researcher conducted an exposition study on the five books, then prepared a design for faith formation materials. The researchers then tested the truth of the material on 20 experts. After analyzing quantitative and qualitative data, the research results were obtained in the form of a faith formation module through the introduction of God's character at the Bekasi Truth Christian Church Sunday School with a material and presentation accuracy value of 92.1% or can be interpreted as very good.